Miller-Fisher syndrome during pregnancy - Reyna-Villasmil, Eduardo (2022)
Miller-Fisher syndrome is a rare, acute, autoimmune, demyelinating disorder whichis considered a variant of Guillain-Barré syndrome. The pathologic mechanism isunclear, but acute demyelinating polyneuropathies may be triggered by bacterialor viral infections, major surgical interventions, or vaccination. Pregnancy may bea trigger of the immune response causing the onset of the syndrome. Miller-Fishersyndrome is characterized by acute onset, with predominant involvement of the facialand cranial nerves resulting in ophthalmoparesis, ataxia, and areflexia/hyporeflexia.Diagnosis is based on clinical suspicion together with the determination of specificganglioside antibodies and other laboratory and imaging tests. Treatment consistsof intravenous immunoglobulin and plasmapheresis, together with supportivemeasures. There are few reports of the syndrome occurring in pregnant women. Acase of Miller-Fisher syndrome during pregnancy is presented.